Multiconfiguration time-dependent Hartree approach to study the OH+H2 reaction - Bhattacharya, Sayak; Panda, Aditya N.; Meyer, Hans-Dieter (The journal of chemical physics, 2010)
Full dimensional quantum scattering calculations have been carried out for the - OH+ - H - 2 - → - H - 2 - O+H - OH+H2→H2O+H - reaction on the Walch-Dunning-Schatz-Elgersma and Yang-Zhang-Collins-Lee surfaces employing an exact form of the kinetic energy operator. The multiconfiguration time-dependent Hartree (MCTDH) method has been used to perform the wave packet propagations. The MCTDH method uses relatively little memory and its numerical effort scales much more slowly with the dimensionality of the system compared to conventional propagation methods. The reaction probabilities and cross sections obtained on both the surfaces using the MCTDH method are in good agreement with the previous theoretical results. However, the cross sections on the two surfaces differ significantly as a function of the translational energy of the reagents. The difference in barrier heights for the two surfaces along with the transition state structures account for the different reaction probabilities obtained over the entire energy range considered.
Im Titel ist "2" tiefgestellt
Gesehen am 01.02.2023